2007
DOI: 10.1021/es071800d
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Flame Retardant Tetrabromobisphenol A by Singlet Oxygen

Abstract: Wide use of flame retardants can pose an environmental hazard, and it is of interest to investigate how they may degrade. We report here that 3,3',5,5'-tetrabromobisphenol A (TBBPA) is subject to photosensitized oxidation involving singlet molecular oxygen ((1)O2). By using visible light and rose bengal or methylene blue as 102 photosensitizers, we have found that TBBPA is a 102 quencher. The quenching rate constant, k(q), depends on TBBPA ionization (pK = 7.4). In acetonitrile, where TBBPA is undissociated, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
48
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 39 publications
7
48
0
1
Order By: Relevance
“…Specifically, MEHP did not significantly affect DCF fluorescence in either HBSS or RPMI assay solutions lacking serum when compared to the solvent control in the same type of assay solution. Additionally, similar to previous research demonstrating that type of assay solution can impact DCF fluorescence (Han, et al, 2008; Han, et al, 2009; Kalinich, et al, 1997; Korystov, et al, 2007), we observed significantly lower DCF fluorescence for all treatment groups when HBSS was used as the buffer compared to RPMI or RPMI + serum.…”
Section: Discussionsupporting
confidence: 90%
“…Specifically, MEHP did not significantly affect DCF fluorescence in either HBSS or RPMI assay solutions lacking serum when compared to the solvent control in the same type of assay solution. Additionally, similar to previous research demonstrating that type of assay solution can impact DCF fluorescence (Han, et al, 2008; Han, et al, 2009; Kalinich, et al, 1997; Korystov, et al, 2007), we observed significantly lower DCF fluorescence for all treatment groups when HBSS was used as the buffer compared to RPMI or RPMI + serum.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore the debromination accounted only for a part of the degradation mechanism and in addition another degradation mechanism was involved. These results are similar with the studies on the degradation of TBBPA by oxidation, photochemical transformation and catalytic degradation, in which the reactions were dominated by a radical mechanism [55][56][57].…”
Section: With 6 Relativelysupporting
confidence: 89%
“…8) which was possibly the precursor of products A and B, resulting from its dehydrogenation or reaction with methanol during the extraction. A similar observation of radical M and product B was reported in the study of oxidation and photochemical transformation of TBBPA, in which a radical reaction were proven [56,61]. Therefore, during the MC process of Fe + SiO 2 , the zero valent iron could get activated to give electrons and quartz could generate radicals, both of which would make the reaction with target pollutants take place.…”
Section: Proposed Degradation Pathwaysupporting
confidence: 74%
“…The degradation of TBBPA by 1 O 2 was well-studied by Bilski and will be described in the following part. 28 Interestingly, TBBPA exhibited significant photolysis under N 2 atmosphere with a rate slightly lower than that under air atmosphere, as shown in Figure 2A. The results indicated that dissolved oxygen was not required for the photolysis of TBBPA.…”
Section: Materials Andmentioning
confidence: 89%